The relationship between general causality orientation and treatment outcome among marijuana-dependent adults. (February 2016) - Blevins, Claire E.; Banes, Kelsey E.; Walker, Denise D.; Stephens, Robert S.; Roffman, Roger A.
Abstract: General causality orientations are motivational styles that are indicative of a person's belief about personal change and their motivation to change. The purpose of the current study was to investigate whether causality orientations were associated with marijuana treatment outcomes in a sample of marijuana-dependent individuals. A total of 74 participants (66% male) were recruited from the Seattle, Washington area and randomly assigned to receive a combination of motivational enhancement and cognitive behavioral therapy or the combination treatment plus additional "check-up" sessions. Follow-up assessments evaluated frequency of use, use-related problems, and marijuana use disorder symptoms through 9 months. Causality orientations were relatively stable over time. Posttreatment Autonomy orientations were associated with lower frequency of use and Controlled orientations were associated with a reduction in use, problems, and marijuana use disorder symptoms. Autonomy and Controlled orientations were associated with readiness to change. Results suggest that both autonomous and controlled orientations have implications for response to treatment; perhaps for different reasons. Causality orientations may be a promising avenue of research to predict treatment response and outcome. Highlights: General causality orientations classify motivational styles into three orientations Outcomes from a marijuana treatment trial were examined according to orientation Posttreatment causality orientations were associated with differential outcomes